2019
DOI: 10.1038/s41598-019-52908-w
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin mediates hypoferremia and reduces the growth potential of bacteria in the immediate post-natal period in human neonates

Abstract: Septicemia is a leading cause of death among neonates in low-income settings, a situation that is deteriorating due to high levels of antimicrobial resistance. Novel interventions are urgently needed. Iron stimulates the growth of most bacteria and hypoferremia induced by the acute phase response is a key element of innate immunity. Cord blood, which has high levels of hemoglobin, iron and transferrin saturation, has hitherto been used as a proxy for the iron status of neonates. We investigated hepcidin-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 25 publications
6
26
0
Order By: Relevance
“…This study reported a much higher cord blood hepcidin value (67.9 ng/mL; 95% CI: 59.3, 76.5 ng/mL), as Supplemental Figure 1A shows. In addition, this study also recorded higher hepcidin concentrations in venous samples collected at 72 h (92.9 ng/mL; 95% CI: 83.3, 102.3 ng/mL) ( 46 ) than in those collected by Prentice et al ( 99 ) at 77 h (55.6 ng/mL; 95% CI: 47.1, 65.5 ng/mL).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…This study reported a much higher cord blood hepcidin value (67.9 ng/mL; 95% CI: 59.3, 76.5 ng/mL), as Supplemental Figure 1A shows. In addition, this study also recorded higher hepcidin concentrations in venous samples collected at 72 h (92.9 ng/mL; 95% CI: 83.3, 102.3 ng/mL) ( 46 ) than in those collected by Prentice et al ( 99 ) at 77 h (55.6 ng/mL; 95% CI: 47.1, 65.5 ng/mL).…”
Section: Discussionsupporting
confidence: 58%
“… Standardized hepcidin over the neonatal period. (A) Full-term neonates: α shows the weighted mean (95% CI) for all studies seen in Supplemental Figure 1A; β, χ, and ε show Prentice et al ( 99 ); δ shows Kulik-Rechberger et al ( 46 ). (B) Preterm neonates: α shows the weighted mean (95% CI) for all studies seen in Supplemental Figure 1B; β shows Uijterschout et al ( 100 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations